2021
DOI: 10.12688/hrbopenres.13325.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence synthesis summary formats for clinical guideline development group members: a mixed-methods systematic review protocol

Abstract: Introduction: Evidence syntheses, often in the form of systematic reviews, are essential for clinical guideline development and informing changes to health policies. However, clinical guideline development groups (CGDG) are multidisciplinary, and participants such as policymakers, healthcare professionals and patient representatives can face obstacles when trying to understand and use evidence synthesis findings. Summary formats to communicate the results of evidence syntheses have become increasingly common, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Our focus group workshops allowed us to create a more practical list of recommendations that was co-designed with multidisciplinary clinical guideline development group members who use and create evidence synthesis summaries for decision-making. Our study's findings largely confirmed the 94 MMSR recommendations [8] and condensed them into more practical guidance containing 21 items. The guidance for summary producers generated from this research, emphasizes a "less-is-more" approach that avoids academic technical language, limits methodological information, and highlights the key conclusions or recommendations framed within the appropriate context.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our focus group workshops allowed us to create a more practical list of recommendations that was co-designed with multidisciplinary clinical guideline development group members who use and create evidence synthesis summaries for decision-making. Our study's findings largely confirmed the 94 MMSR recommendations [8] and condensed them into more practical guidance containing 21 items. The guidance for summary producers generated from this research, emphasizes a "less-is-more" approach that avoids academic technical language, limits methodological information, and highlights the key conclusions or recommendations framed within the appropriate context.…”
Section: Discussionsupporting
confidence: 76%
“…This list has been co-created in collaboration with members of multidisciplinary clinical guideline development groups, who are well-versed in using and creating evidence synthesis summaries to aid decision-making. Our practical guidance of 21 items aligns with and has streamlined the 94 MMSR recommendations [8]. As we move forward, we intend to develop and user-test the prototype templates through detailed oneon-one semi-structured interviews.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This may reflect heterogeneity in development methods that could be addressed by rigorously using the GRADE evidence-to-decision framework, AGREE guidelines, and evidence synthesis summary formats to collate evidence. 32 Good In pediatric patients with blunt renal trauma, we strongly recommend routine blood pressure checks on follow up to diagnose hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Despite relatively uniform ratings of low quality of evidence for abstracted recommendations, EAST/PTS systematically rated all recommendations as strong using the GRADE method, whereas WSES and APSA uniformly graded recommendations with low-quality evidence as weak. This may reflect heterogeneity in development methods that could be addressed by rigorously using the GRADE evidence-to-decision framework, AGREE guidelines, and evidence synthesis summary formats to collate evidence 32 . Good practice statements, developed using GRADE methodology, 33,34 are an interesting alternative to formal graded recommendations when no direct evidence is available.…”
Section: Discussionmentioning
confidence: 99%